Emergency General Surgery: Defining Burden of Disease in the State of Maryland. Issue 8 (August 2015) - Bruns, Brandon R.; Tesoriero, Ronald; Narayan, Mayur; Klyushnenkova, Elena N.; Chen, Herbert; Scalea, Thomas M.; Diaz, Jose J.
Acute care surgery services continue expanding to provide emergency general surgery (EGS) care. The aim of this study is to define the characteristics of the EGS population in Maryland. Retrospective review of the Health Services Cost Review Commission database from 2009 to 2013 was performed. American Association for the Surgery of Trauma-defined EGS ICD-9 codes were used to define the EGS population. Data collected included patient demographics, admission origin [emergency department (ED) versus non-ED], length of stay (LOS), mortality, and disposition. There were 3, 157, 646 encounters. In all, 817, 942 (26%) were EGS encounters, with 76 per cent admitted via an ED. The median age of ED patients that died was 74 years versus 61 years for those that lived ( P < 0.001). Twenty one per cent of ED admitted patients had a LOS > 7 days. Of 78, 065 non-ED admitted patients, the median age of those that died was 68 years versus 59 years for those that lived ( P < 0.001). Twenty eight per cent of non-ED admits had LOS > 7 days. In both ED and non-ED patients, there was a bimodal distribution of death, with most patients dying at LOS ≤ 2 or LOS > 7 days. In this study, EGS diagnoses are present in 26 per cent of inpatient encounters in Maryland. The EGS population is elderly with prolonged LOS and a bimodal distribution of death.